2020
DOI: 10.1186/s12888-020-02876-7
|View full text |Cite
|
Sign up to set email alerts
|

Correction to: The prevalence and associated factors of alcohol use among pregnant women attending antenatal care at public hospitals Addis Ababa, Ethiopia, 2019

Abstract: An amendment to this paper has been published and can be accessed via the original article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 1 publication
0
1
0
Order By: Relevance
“…The main characteristics of all included studies presented in S3A and S3B Table . Overall, 7 studies assessed khat use only [6,7,10,[38][39][40][41], and 12 studies assessed alcohol consumption only [21,[24][25][26][27][28][29][30][31][32][33][34], and 4 studies assessed both khat and alcohol use during pregnancy [19,20,22,38]. These studies were all cross-sectional and conducted in 5 regions of Ethiopia between 2014 and 2020.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…The main characteristics of all included studies presented in S3A and S3B Table . Overall, 7 studies assessed khat use only [6,7,10,[38][39][40][41], and 12 studies assessed alcohol consumption only [21,[24][25][26][27][28][29][30][31][32][33][34], and 4 studies assessed both khat and alcohol use during pregnancy [19,20,22,38]. These studies were all cross-sectional and conducted in 5 regions of Ethiopia between 2014 and 2020.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Several alcohol use epidemiological studies among pregnant women are available in Ethiopia. However, the results of these studies showed a wide variation of prevalence ranging from 4.10 to 76.70% [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] over time and across geographical areas. Similarly, a national study conducted using Ethiopian Demographic Health Survey (EDHS) 2016 data showed that the spatial distribution of alcohol consumption was highly variable across the country.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alcohol is a psychoactive substance with several neurobiological effects that can cause both acute and chronic injury in the brain, including neuroin ammation and neurodegeneration [7]. Further, microglia, a resident macrophage of the CNS, can be activated in the brain after excessive alcohol intake [8].…”
Section: Introductionmentioning
confidence: 99%